2011
DOI: 10.2174/1874140101105010045
|View full text |Cite
|
Sign up to set email alerts
|

Mechanoluminescence of Nanoparticles

Abstract: Certain nanoparticles exhibit intense light emission during their elastic deformation, called the phenomenon of elastico mechanoluminescence (EML).When ZnS:Mn and SrAl 2 O 4 :Eu nanoparticles are deformed in the elastic region by the stress initially increasing with time and then attaining a fixed value or by the stress initially increasing and then decreasing with time or by the impact stress, then after a threshold pressure, initially the EML intensity increases with time, attains a maximum value and later o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…In subsequent work, Xu et al made a significant development by using a thin film of ZnS:Mn nanoparticles as stress indicators. [12][13][14][15][16][17][18] The film with the strongest mechanoluminescence consisted of nano-sized crystallites of ZnS doped with 1.5 wt.% Mn, in which Mn acted as the emitting center. Because of its high PL efficiency and stability at ambient temperature there is much interest in ZnS:Mn.…”
Section: Introductionmentioning
confidence: 99%
“…In subsequent work, Xu et al made a significant development by using a thin film of ZnS:Mn nanoparticles as stress indicators. [12][13][14][15][16][17][18] The film with the strongest mechanoluminescence consisted of nano-sized crystallites of ZnS doped with 1.5 wt.% Mn, in which Mn acted as the emitting center. Because of its high PL efficiency and stability at ambient temperature there is much interest in ZnS:Mn.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the impact sample gets fractured and the creation new surfaces give rise to local and piezoelectricity, may be a reason for ML emission. This fracto-mechanoluminescent material can be helpful in designing the fracto-ML based devices such as fracture sensor, impact sensor, damage sensors, safety management monitoring system, fuse system for army warheads, etc (Chandra, 2011(Chandra, , 2012.…”
Section: Resultsmentioning
confidence: 99%
“…They are often used as an example material when presenting afterglow mechanisms and they are the most widely studied persistent luminescent silicates (Chandra, 1998(Chandra, , 2011(Chandra, , 2012Kim, Kwon, & Sohn, 2013). It has been already reported that light emission takes place during the elastic deformation, plastic deformation and fracture of solids.…”
Section: Introductionmentioning
confidence: 99%
“…first peak is observed. In this case the time related to the first peak becomes comparable with the time needed for the de-trapping of the electrons from the traps (Chandra, 2011;Koto et al, 2002;Park & Seo, 2014).…”
Section: Mechanoluminescence Studymentioning
confidence: 95%